MARCAS DE UM JORNALISMO REGIONAL: IDENTIDADE CULTURAL GAÚCHA NOS DIÁRIOS PARANAENSES - Jasper, Aline (2016)
With the emergence of a global society, the way cultural identities are structured changes. While the globalization processes integrate and interconnect societies, they also generate actions that reinforce the regional scope as means to resist global homogenization. Regional journalism has a fundamental role in revaluating singularities and regionalisms, as well as the shaping of identities and culture‟s portrayal in media. Based in the relation of proximity with readers, regional press has the possibility of approaching topics of interest to the community it belongs to. In Southern Brazil, gaucho cultural identity has established survival strategies and spread to other regions, like Paraná. Multicultural in its essence, the State of Paraná was shaped by successive colonization fronts that caused cultural identification to happen differently in each region of the state. Mainly with tropeirismo and the colonization in Western Paraná, gaucho culture took root and was adapted, modified and assimilated by Paraná‟s people. Using quantitative and qualitative methodologic references, this research aimed to verify how eleven daily newspapers from different regions of the state approach gaucho culture in their pages in two distinct moments:between 13 and 27 September 2014 and 2015. The choice of date was made based on the relevance of September 20 to gauchismo and on the celebrations of SemanaFarroupilha, performed on the first week of the analysis, that mobilize traditionalist entities to promote events. Analyzing the data, it could be perceived how regional specificities and the characteristics of regional journalism interfere in the treatmentgiven by the diaries to this theme. Amongst the findings, it was found that the larger the cities and newspaper runs, the smaller the amount of references to gaucho culture, very likely because of the cultural diversity that comes from larger public. It was also found that, in Western and Southwestern Paraná, more news is published about gauchismo, because of the particularities of settlement in the region. Also, the news coverage of this theme, in the same direction as Brazilian cultural journalism, features only cultural agenda, with little questioning of subjects, whose approach is often centered in describing events, with limited editorial diversity.